2012
DOI: 10.1371/journal.pone.0044604
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Postural Indicator of Back Pain in Horses (Equus caballus)

Abstract: Postures have long been used and proved useful to describe animals’ behaviours and emotional states, but remains difficult to assess objectively in field conditions. A recent study performed on horses using geometric morphometrics revealed important postural differences between 2 horse populations differing in management conditions (leisure horses living in social groups used for occasional “relaxed” riding/riding school horses living in individual boxes used in daily riding lessons with more constraining tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(91 citation statements)
references
References 60 publications
8
83
0
Order By: Relevance
“…Instead, to reach large sample sizes most studies rely on questionnaires sent to owners or caretakers or self-reports (Hotchkiss et al, 2007;Murray et al, 2010;Ireland et al, 2012;Lesimple et al, 2012). However, several authors have shown that the effectiveness of this method is debatable since the response rate may be positively biased (e.g., toward less problems) and owner or caretakers may severely underestimate possible health and welfare problems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, to reach large sample sizes most studies rely on questionnaires sent to owners or caretakers or self-reports (Hotchkiss et al, 2007;Murray et al, 2010;Ireland et al, 2012;Lesimple et al, 2012). However, several authors have shown that the effectiveness of this method is debatable since the response rate may be positively biased (e.g., toward less problems) and owner or caretakers may severely underestimate possible health and welfare problems.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological or painful conditions such as lameness, sore mouth, and back pain can arise through injury associated with inadequate housing, management, activities, and equipment (Wyse et al, 2008;Lesimple et al, 2010;McGowan et al, 2010;Murray et al, 2010;Ireland et al, 2012;Lesimple et al, 2012). Lameness was a frequently reported health problem by owners of dressage horses in the study of Murray et al (2010): 33% of the horses were lame at some time during their career.…”
Section: Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Their observations reveal potential « candidates » such as the quality of the human-horse relationship or the attentional state. More recently, studies by Fureix et al (2012Fureix et al ( , 2015, Lesimple et al (2012Lesimple et al ( , 2013Lesimple et al ( , 2014, Rochais et al (2016a,b) have led to the emergence of visible (behavioural and physiological) indicators that converge with evaluations of physiological and sanitary measures. Because the perception of situations is subjective, using such indicators, allow an animal-centered approach that can help identify the factors of influence and their relative weight in determining horse welfare, (Lesimple et al in revision).…”
Section: Application Improving Management Capabilitymentioning
confidence: 99%